A Network-Based Method for Mechanistic Investigation and Neuroprotective Effect on Post-treatment of Senkyunolid-H Against Cerebral Ischemic Stroke in Mouse - Zhang, Jie; Jiang, Yunyao; Liu, Nan; Shen, Ting; Jung, Hyo Won; Liu, Jianxun; Yan, Bing Chun (Frontiers in Neurology, 2019)
Senkyunolide-H (SEH), a major bioactive compound extracted from Ligusticum chuanxiong, has been reported to be effective prevent cerebral ischemic stroke (CIS). In this study, we employed network pharmacology to reveal the potential mechanism of SEH against CIS on a system level, and confirmed the therapeutic effects of SEH in CIS by a mouse model of cerebral ischemia–reperfusion (I/R). Through protein-protein interaction (PPI) networks construction of SEH and CIS related targets, a total of 62 key targets were obtained by screening topological indices and analyzed for Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment. GO analysis indicated that SEH might have a role in treating CIS via regulating some biological processes including regulation of transcription from RNA polymerase II promoter, epidermal growth factor receptor signaling pathway, phosphatidylinositol-mediated signaling, and some molecular function, such as transcription factor binding, protein phosphatase binding, nitric oxide synthase regulator activity. Meanwhile, KEGG analysis showed that phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway was significantly enriched. In addition, our result showed SEH post-treatment significantly decreased the neurological scores, infarct volume and neuronal death in the MCAO mice. Moreover, the PI3K/Akt/NF-κB signaling pathway was activated by intragastric administration of 40 mg/kg SEH, as verified by Western blot. In summary, the results suggested that SEH carries a therapeutic potential in CIS involved multiple targets and pathways, and the most crucial mechanism might be via activation of the PI3K/Akt/NF-κB signaling pathway to inhibit inflammatory factor releases and increase the anti-apoptosis capacity. Our study provides a network pharmacology framework for future research on traditional Chinese medicine.